Marketing Strategy of Narapati Indah Syariah Hotel - Nurahman, Gari; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2013)
In 1992, the formation of Muamalat Bank as the first bank that based on syariâ€™ah in Indonesia is the starting point of growth and development of syariâ€™ah economic paradigm factually in Indonesia. So did in the global capital markets, the Western views this as one ethycal invesment or business of ordinary course, who enchase commercial values of a business with certain values. Meanwhile, the hospitality business as business engaged in accommodation services are maintained commercially is basically one other businesses, clean. However, because the tendencies of hedonistic desire, there were a lot ofÂ  â€œpersonâ€ of hotel business whoÂ  shifting to the practice that contradicting to the governmental regulations, and from religious side, it becomes an â€œimmoralâ€ value. Regardless of all phenomenas, Ahmad Gemma Nurrahman as a General Manager of Narapati Hotel, motivated by his desire to make his hotel as a first hotel that applying syariah values, at the end of 2011 proposed an idea to convert the system and mechanism of his hotel management into the hotel that applying the syariah values. Until the end of 2011, the occupancy level of Narapati Indah Hotel & Convention average reached 62 %. But if it is compared in 2008 which reached 62.29 %, it means a significant decline. In 2012, after applying the label and values of â€œSyariahâ€ beginning from the name to all activities implemented, so the point will has an impact on the loss of potential customers in the side and the emergence of potential on the other hand. The current question is, how to increase of Narapati Indah Hotel & Convention occupance with the customers who have morrality? Unclear STP make lack of differentiation. With no differentiation make the awareness became low, thatâ€™s the main reasons why Narapati Indah Syariah Hotel & Convention have a low occupancy level, beside of highly industrial competition is also became the other reason. The main thing to be done is to improve Occupancy Rate as desired by management of Narapati syariah Hotel & Convention is do proper marketing communication to build awareness of syariah hotel, defined new STP for syariah hotel, and reinforce the marketing effort in marketing mix, especially product, process, physical evidence and also Promotion.Â Keywords: Syariah hotel, low occupancy,Unclear STP,Islamic hotelÂ